B cell activation involves nanoscale receptor reorganizations and inside-out signaling by Syk - Kläsener, Kathrin; Maity, Palash C; Hobeika, Elias; Yang, Jianying; Reth, Michael (eLife, 2014)
Binding of antigen to the B cell antigen receptor (BCR) initiates a multitude of events resulting in B cell activation. How the BCR becomes signaling-competent upon antigen binding is still a matter of controversy. Using a high-resolution proximity ligation assay (PLA) to monitor the conformation of the BCR and its interactions with co-receptors at a 10–20 nm resolution, we provide direct evidence for the opening of BCR dimers during B cell activation. We also show that upon binding Syk opens the receptor by an inside-out signaling mechanism that amplifies BCR signaling. Furthermore, we found that on resting B cells, the coreceptor CD19 is in close proximity with the IgD-BCR and on activated B cells with the IgM-BCR, indicating nanoscale reorganization of receptor clusters during B cell activation.
Keywords: B cell antigen receptor; nanoscale receptor organization; inside-out signaling